E-Portfolio Assessment in Language Learning: Exploring Students’ Perceptions and the Development of Self-Assessment Skills in EFL Classroom - Fatima, St. Nur Aima; Syahrullah, Syahrullah (English Education Postgraduate Program, Universitas Negeri Manado, 2025)
This research investigates how e-portfolio assessment is perceived by students and how it helps them develop self-assessment abilities in the EFL classroom. The research adopted qualitative descriptive case research method for an in-depth exploration of students’ perceptions and development of self-assessment skill regarding e-portfolio assessment in EFL classroom at STAI Al-Gazali Bone. Data were gathered using a semi-structured interview consisting ten questions to measure the Students’ Perceptions of the benefits and challenges of using e-portfolio assessment in the EFL classroom. The findings of this research reveal that e-portfolio assessment has a significant impact on students’ learning experiences in the EFL classroom, particularly in enhancing self-assessment, motivation, and engagement. Students generally expressed positive perceptions toward the use of e-portfolio, citing its flexibility, ease of access, and ability to accommodate a variety of task formats (text, audio, video) as major benefits. Another important finding is the development of self-assessment skills. Students engaged in reflective activities, such as reviewing their progress, comparing their work with peers, and analyzing feedback. Despite the benefits, students also reported several challenges. Technical issues such as unstable internet connections and unclear instructions were common obstacles. In summary, while e portfolio assessment offers meaningful advantages for language learning and reflective practice, its effectiveness depends on how it is implemented, the support provided by lecturers, and the technological readiness of both students and the institution. Keywords: E-portfolio assessment, self-assessment, students’ perception, EFL classroom